2018
DOI: 10.1590/s1517-707620180004.0601
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo entre PETG e PLA para Impressão 3D através de caracterização térmica, química e mecânica

Abstract: RESUMO A Impressão 3D baseada em extrusão se popularizou muito nos últimos anos devido ao surgimento de projetos de código aberto e máquinas de baixo custo, que tornaram a tecnologia acessível a todos os níveis de usuários. Paralelamente, novos materiais, em geral filamentos termoplásticos, são inseridos no mercado para aplicação neste tipo de técnica de fabricação, tornando cada vez mais necessário o desenvolvimento de estudos de caraterização experimentais dos materiais para fornecer dados técnicos aos utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 61 publications
2
30
0
8
Order By: Relevance
“…On comparing 3D printed PETG with its injectionmolded counterparts and PLA, it is evident that the injection-molded specimens exhibited better properties due to better adhesion and uniform properties. [19] The 3D printed PETG parts showed about a 10% decrease in the overall tensile strength when compared to the injection-molded part even when printed unidirectionally at 0 . Though 3D printed PLA showed an improved tensile strength of about 6-8% as compared to their PETG counterparts in the 0 direction, their low thermal properties often limit their applicability in practical scenarios.…”
Section: Introductionmentioning
confidence: 93%
“…On comparing 3D printed PETG with its injectionmolded counterparts and PLA, it is evident that the injection-molded specimens exhibited better properties due to better adhesion and uniform properties. [19] The 3D printed PETG parts showed about a 10% decrease in the overall tensile strength when compared to the injection-molded part even when printed unidirectionally at 0 . Though 3D printed PLA showed an improved tensile strength of about 6-8% as compared to their PETG counterparts in the 0 direction, their low thermal properties often limit their applicability in practical scenarios.…”
Section: Introductionmentioning
confidence: 93%
“…The PETG characteristics according to [7,33,42], present values for the maximum load related to the elasticity area, taking into account the variation: wall thickness, printing speed, extrusion cooling conditions and printing bed temperature. From what is presented, it is concluded that the chassis elements of ROUV are better to be made, through 3D Printing technology, from PETG.…”
Section: Considerations For Tensile Testing In Order To Choose the Mamentioning
confidence: 99%
“…The construction plan used for the PB manufacturing was the XYZ plan, represented in Figure 3 below. Regarding the references of XYZ and YXZ print directions, better mechanical resistance and, at the end of the print, good dimensional precision in the printed body were achieved with FDM technology [23][24][25]. For the manufacture of PB and execution of the tensile test of this work, it was considered as a controlled parameter the density of infill in Tri-Hexagonal format, obtained by Cura Ultimaker software version 3.6.0.…”
Section: Printing Parametersmentioning
confidence: 99%
“…Parts made using three-dimensional printing have variable dimensions, as a result of the printing plane and the geometric elements. On the other hand, the components printed in the horizontal plane [22], gives better dimensional accuracy to the printed body [23,24]. That is, when printing on the XYZ plane [22], it was allowed to have the reliable dimensionally sized prosthesis parts with low R_a roughness values not exceeding 25 µm.…”
Section: Device Printingmentioning
confidence: 99%
See 1 more Smart Citation